2017
DOI: 10.5194/angeo-35-567-2017
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal MLT-region nightglow intensities, temperatures, and emission heights at a Southern Hemisphere midlatitude site

Abstract: Abstract. We consider 5 years of spectrometer measurements of OH(6-2) and O 2 (0-1) airglow emission intensities and temperatures made near Adelaide, Australia (35 • S, 138 • E), between September 2001 and August 2006 and compare them with measurements of the same parameters from at the same site using an airglow imager, with the intensities of the OH(8-3) and O( 1 S) emissions made with a filter photometer, and with 2 years of Aura MLS (Microwave Limb Sounder) v3.3 temperatures and 4.5 years of TIMED SABER (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…In contrast, the reversal near 80 km is caused by the neutralization of meteoric plasma in addition to ambipolar diffusion (Lee et al, ; Younger et al, ). The height of the lower inflection point can be used as a tool for measuring the height of a constant density surface (Reid et al, ; Younger et al, ). It should be noted that values of log 10 D derived from the KMMR show excellent agreement with the independent SABER measurements near 90 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the reversal near 80 km is caused by the neutralization of meteoric plasma in addition to ambipolar diffusion (Lee et al, ; Younger et al, ). The height of the lower inflection point can be used as a tool for measuring the height of a constant density surface (Reid et al, ; Younger et al, ). It should be noted that values of log 10 D derived from the KMMR show excellent agreement with the independent SABER measurements near 90 km.…”
Section: Discussionmentioning
confidence: 99%
“…However, accurate knowledge of neutral atmospheric density in the MLT region is essential for studying the dynamics and climate of the middle atmosphere, including shorter‐term wave motions, such as gravity waves, tides, and planetary waves, as well as long‐term changes, such as interannual variations, seasonal variations, and intraseasonal variations (Stober et al, , ; Younger et al, ). Furthermore, neutral atmospheric density measurements are critical for the correct interpretation of O, O 2 , and OH airglow measurements of atmospheric temperature in the MLT region (Reid et al, ; Takahashi et al, ). Knowledge of the change in neutral atmospheric density over time is crucial information for determining the atmospheric drag on low Earth orbit satellites and directly governs the orbit cycles of satellites; moreover, safe launches and precise landings of spacecraft also require an accurate knowledge of neutral atmospheric density in the MLT region.…”
Section: Introductionmentioning
confidence: 99%
“…The temperatures, winds and densities in the mesopause region are essential for studying the dynamics and climate, including both short-term wave motions (e.g., gravity waves, tides and planetary waves) and long-term climate variations (e.g., interannual variations, seasonal variations and intraseasonal variations), of the middle and upper atmosphere. The climatology of the temperature and wind within the mesopause region has been studied for decades using ground-based instruments such as meteor radars, mediumfrequency (MF) radars, lidars (Dowdy et al, 2001;Dou et al, 2009;Li et al, 2008Li et al, , 2012Li et al, , 2018 and satellite instruments (Garcia et al, 1997;Remsberg et al, 2002;Xu et al, 2007). It is well established that the semiannual oscillation (SAO) dominates the seasonal variations in both the wind and the temperature in the low-latitude mesosphere (Li et al, 2012), whereas the annual oscillation (AO) dominates the seasonal variations in the mid-and high-latitude mesosphere (Remsberg et al, 2002;Xu et al, 2007;Dou et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The climatology of the temperature and wind within the mesopause region has been studied for decades using ground-based instruments such as meteor radars, mediumfrequency (MF) radars, lidars (Dowdy et al, 2001;Dou et al, 2009;Li et al, 2008Li et al, , 2012Li et al, , 2018 and satellite instruments (Garcia et al, 1997;Remsberg et al, 2002;Xu et al, 2007). It is well established that the semiannual oscillation (SAO) dominates the seasonal variations in both the wind and the temperature in the low-latitude mesosphere (Li et al, 2012), whereas the annual oscillation (AO) dominates the seasonal variations in the mid-and high-latitude mesosphere (Remsberg et al, 2002;Xu et al, 2007;Dou et al, 2009). However, in contrast to temperature and wind observations, longterm continuous measurements of the atmospheric density in the mesopause region are still quite rare; as a result, the seasonal variations in the mesopause, especially with regard to its global structure, are still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sudden stratospheric warmings alter the OH altitude, producing up to 10 km vertical shifts during the descent phase (Shepherd et al, 2010b). On a medium timescale, the seasonal variation in the emission altitudes exhibits semiannual, annual and quasi-biennial oscillations with up to 1.0, 1.5 and 0.5 km amplitudes, respectively (Winick et al, 2009;Gao et al, 2010;Sheese et al, 2014;von Savigny, 2015;Reid et al, 2017). Ghodpage et al (2016) and Sivakandan et al (2016) reported a year-to-year monthly mean OH altitude variation of 2-3 km and attributed it to the effect of the El Niño-Southern Oscillation (ENSO).…”
Section: Introductionmentioning
confidence: 99%